Effect of a quality-improvement intervention on end-of-life care in cardiac intensive care unit: a single center experience. (3rd May 2023) - Sacco, A; Ditali, V; Garatti, L; Villanova, L; Colombo, C; Scavelli, F; Viola, G; Lissoni, B; Forni, L; Gorni, G; Oliva, F G
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Fondazione di Comunità Milano. Background: Patients admitted to Cardiac Intensive Care Units (CICUs) have increasingly complex medical conditions; consequently, palliative care (PC) should be an integral component of their management. Although there are robust experiences emanating from other intensive care settings, there has been less discussion about the role of PC in CICUs and the delivery of end-of-life (EOL) care in this context is still very challenging. A 2019 we conducted a survey showing compelling evidence of problems with the quality of EOL care in our Tertiary Referral Hospital's CICU, with physicians often unaware of patients' anticipated directives and very poor involvement of PC. Purpose: To identify educational interventions to enhance EOL care in patients with advanced heart failure (HF) admitted to our CICU. Methods: This is a before–after study showing the effect of interventions for CICU staff on competence in EOL care. The intervention was a multifaceted education program delivered by two trainers: an Associate Professor/philosopher of Law and a Clinical Psychologist. A controlled trial design was undertaken with baseline and 2 years follow-up measurement of both objective and self-perceived competence. The training intervention was a 10 hours face-to-face course involving the following techniques: a) focus group: used as a qualitative tool to identify the team's training needs; b) staff support case: clinical debriefing after challenging EOL cases; c) empowerment of communication skills. Questionnaires completed by participants were used to measure self-perceived competence. Records of all patients died with advanced HF between 2021 and 2022 (31 patients) were obtained to evaluate how therapeutic limitation was managed compared with the survey conducted between 2018 and 2019 (21 patients). The primary outcome measure was the development of objective competence in EOL management in terms of: a) report of therapeutic limitation in the prescription charts; b) adequate analgo-sedation evaluated according to pain and existential suffering control; c) early involvement of PC; d) report of patients'anticipated directives. The secondary outcome was represented by staff clinical improvements in communication, collaboration and shared decision making. Results: See table. Conclusions: A 2019 survey in our CICU showed that the management of advanced HF patients was aggressive. The medical and nursing staff was not sufficiently equipped with adequate practical knowledge as far as it concerns law, ethics and communication techniques. According to these observations we have planned interventions aimed at training our professionals to be knowledgeable, confident and skilled to discuss this kind of questions. After interventions, staff felt more involved and more comfortable, and reported more clarity in transitioning patients; as a consequence, we observed improvement in EOL managing.